2007
DOI: 10.1152/ajpregu.00793.2006
|View full text |Cite
|
Sign up to set email alerts
|

Role of midbrain in the control of breathing in anuran amphibians

Abstract: Gargaglioni LH, Meier JT, Branco LG, Milsom WK. Role of midbrain in the control of breathing in anuran amphibians. Am J Physiol Regul Integr Comp Physiol 293: R447-R457, 2007. First published April 9, 2007; doi:10.1152/ajpregu.00793.2006.-The present study was designed to explore systematically the midbrain of unanesthetized, decerebrate anuran amphibians (bullfrogs), using chemical and electrical stimulation and midbrain transections to identify sites capable of exciting and inhibiting breathing. Ventilation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 28 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…Episodic breathing is expressed in fish, amphibians, reptiles, and some mammals under certain conditions (Milsom, 1991). Factors that regulate or modulate episodic breathing include chemosensory and mechanosensory inputs (Kinkead and Milsom, 1997; Reid et al, 2003) and central structures rostral to the brainstem (Kinkead et al, 1997; Milsom et al, 1997; Reid et al, 2000; Gargaglioni et al, 2007). In ectothermic vertebrates, the capacity for episodic breathing is contained within the isolated brainstems of tadpoles (Straus et al, 2000), bullfrogs (Kinkead et al, 1994; Reid and Milsom, 1998), and turtles (Douse and Mitchell, 1990; Johnson et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Episodic breathing is expressed in fish, amphibians, reptiles, and some mammals under certain conditions (Milsom, 1991). Factors that regulate or modulate episodic breathing include chemosensory and mechanosensory inputs (Kinkead and Milsom, 1997; Reid et al, 2003) and central structures rostral to the brainstem (Kinkead et al, 1997; Milsom et al, 1997; Reid et al, 2000; Gargaglioni et al, 2007). In ectothermic vertebrates, the capacity for episodic breathing is contained within the isolated brainstems of tadpoles (Straus et al, 2000), bullfrogs (Kinkead et al, 1994; Reid and Milsom, 1998), and turtles (Douse and Mitchell, 1990; Johnson et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In frogs, episodic breathing appears to be regulated or modulated by chemosensory and mechanosensory inputs (Kinkead and Milsom, 1997), structures rostral to the brainstem (Kinkead et al, 1997; Milsom et al, 1997; Reid et al, 2000; Gargaglioni et al, 2007), and structures within the brainstem during GABA B receptor blockade (Straus et al, 2000). In contrast, very little is known about mechanisms underlying episodic discharge in turtles other than the fact that some isolated turtle brainstems produce episodic cranial nerve motor bursts (Douse and Mitchell, 1990; Johnson et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggest that pontine nuclei, including Kölliker–Fuse (K-F) and parabrachial (PB) nuclei comprise the pontine respiratory group (PRG), which regulates the inspiratory-expiratory phase transition 31, 32 . Other studies report that neurons in the superior colliculus (SC) 33 , RN 33 , and intermediate reticular nucleus (IRN) 34 also influence the respiratory cycle. In our study we showed that the PB, SC, RN and IRN were extensively infected by RABV regardless of the infection route (Figure 3), suggesting that the abnormal breathing may be related to the neuronal damage caused by RABV infection in these nuclei.…”
Section: Discussionmentioning
confidence: 99%